Participación de la familia en el rendimiento académico en los estudiantes del quinto grado de primaria de la Institución Educativa María Parado de Bellido del distrito de Iquitos en el año 2022 - Solsol Melendez, Maria Luisa (2023)
The objective of the research was to determine the relationship between family participation and academic performance of the fifth grade students of the María Parado de Bellido educational institution, Iquitos - 2022. This study had a quantitative approach, was non-experimental and had a cross-sectional design. The population consisted of 110 students and the sample of 61 students and parents of the fifth grade of primary school. For data collection, the structured interview technique and documentary analysis were used. The instruments used were the questionnaire and the documentary record sheet. The reliability of the instruments was verified using the Cronbach's Alpha coefficient test. For data processing, the statistical program Statistical package for social sciences (SPSS), version 24 in Spanish, and an Excel spreadsheet were used. For the descriptive and inferential analysis of data, frequency, average and percentage, the statistical test of free distribution of the Chi Square (??)2 with ? = 0.05% and confidence level of 0.95% was applied. The data will be presented in tables and bar graphs to facilitate their corresponding interpretation.